Microgravity combustion : fire in free fall - Ross, Howard D. (Combustion treatise., 2001)
This book provides an introduction to understanding combustion, the burning of a substance that produces heat and often light, in microgravity environments-i.e., environments with very low gravity such as outer space. Readers are presented with a compilation of worldwide findings from fifteen years of research and experimental tests in various low-gravity environments, including drop towers, aircraft, and space. Microgravity Combustion is unique in that no other book reviews low- gravity combustion research in such a comprehensive manner. It provides an excellent introduction for researching in the fields of combustion, aerospace, and fluid and thermal sciences.